Analysis of Students' Mathematical Creative Thinking Abilities on Relation and Function Material - Firman Riansyah; Halistin; Dedyerianto; La Boy; Tandri Patih; Musdalifa (FKIP Universitas Halu Oleo, 2024)
The ability to think creatively, especially in mathematics, is highly needed today for the development of science in the 21st century. However, many Indonesian students still find it difficult to develop creativity in solving problems related to relations and functions. This research aims to identify the level of creative thinking ability of eighth-grade students at SMPN 5 Kendari in the material of relations and functions. The methodology used is qualitative. The instrument used is 4 essay questions on mathematical creative thinking ability in the material of relations and functions. These questions include indicators of fluency, flexibility, originality, and elaboration. The results of the study show that most of the eighth-grade A students have good fluency skills, but their flexibility skills still need to be improved. Originality and elaboration skills are also still very low. Meanwhile, the level of mathematical creative thinking ability of eighth-grade A students at SMP Negeri 5 Kendari is in the medium category with 21 students (70%). Based on the results of the above descriptions, it shows that students' mathematical creative thinking abilities based on the distribution of questions are not fully owned and need to be improved.